Characterizing the signaling pathways of nerve growth factor in neuronal stem cells. - Heese, Klaus. (2008)
In recent years it has been noted that the adult brain has the 'self-repair capacity' to replace lost neurons in several regions of the central neural system (CNS), such as the olfactory bulb, hippocampus, adult human subependymal zone and the cortex. Neural stem cells (NSCs) within these neurogenic regions can proliferate and differentiate into neurons or glia, thus providing a tool of replacement cells to those lost during normal cell turnover and after brain injury. Neurogenesis involves the self-renewal and proliferation of NSCs, as well as its differentiation into neurons and glia which are tightly regulated by both intrinsic and extrinsic factors. Newborn neurons and glia then migrate to appropriate regions in the brain, and integrate into neuronal circuits (Heese et al., 2006).